O MAPA ARQUEOLÓGICO PARCIAL E A REVISÃO HISTORIOGRÁFICA A RESPEITO DAS OCUPAÇÕES INDÍGENAS PRÉ-HISTÓRICAS NO MUNICÍPIO DE PORTO ALEGRE, RIO GRANDE DO SUL (Revista de História Regional, 2007)
This paper presents the first steps of a regional research wich final goal is the understanding of how different populations occupied the same space during the last 10.000 years. For that, theoretical-methodological devises from Archeology, Ethnology and History were used.